(untitled) (Research, Society and Development, 2023)
The use of pozzolanic materials, such as silica, in the construction industry, especially when replacing part of the cement in concrete production, represents a practice that contributes to environmental sustainability. This plays an important role in decreasing CO2 emissions into the atmosphere. Silicas allow the reduction of the amount of cement required in the production of concrete, which results in double environmental preservation. This occurs not only due to the reduction in the extraction of clinker used in the manufacture of cement, but also due to the use of waste from other industries. The use of silica can also improve the properties of concrete. Therefore, through experimental exploratory research, the purpose of this study was to analyze the mechanical performance of Portland cement concrete, in which Portland cement was partially replaced by silica from rice husk ash (rh-SiO2). The results showed that the compressive strength of concrete achieved significant gains mainly with the partial replacement of cement with (rh-SiO2) at levels of 15% and 20%.